Proposal of the FinTech's Services Adoption Measurement Model - Souza, Matheus Vieira de; Ribeiro da silva, Hermes Moretti [UNESP]; Spers, Eduardo Eugenio (Pontificia Univ Catolica Sao Paulo-puc-sp, 2021)
Y This study proposes a systematic literature review seeking: What factors influence the adoption of a fintech? From the selected database, 70% are works published in high-impact journals. The most used method was structural equation modeling to assess the development of theoretical constructions from latent constructs. From the attitude factors adopted, the constructs of product design, social influence, privacy, trust, perceived ease of use, perceived as the primary constructs that influence the intention to use and adopt fintech services. In the end, a model for measuring the adoption of fintech services is proposed, which includes these constructs.
Keywords: fintechs; consumer behavior; intention to use; adoption